The Process of Forming Communicative Competence in Future Educators in the Process of Vocational Training - Kosimov Muzaffar Shahobaliyevich (Researchparks Publishing, 2021)
The process of formation of communicative competence in future educators in the process of professional training reveals the conditions of pedagogical conditions